Information System on Road Conditions in Croatia- Plans of Development - Jenić, Vinko; Viduka, Krešimir; Zovak, Goran (Promet - Traffic&Transportation, 2012)
The quality of information about road conditions in theRepublic of Croatia do nor meet the needs of their users- roadvehicle mororists, regarding their content, updating criteria andtimely announcement and warning of potential risks for thedrivers. Neither do they meet the criteria of monitoring and supportduring poor traffic and weather conditions. The paper considerscritically the cwTent situation in the information systemabout the road conditions in the Republic of Croatia, and studiesthe reasons for such a condition. It also gives guidelines forimproving the level of quality of this service and the plans for itsdevelopment. It mentions the activities that should be carriedout in order to improve the whole information system regardingupgrading oft he current system in the segments of receiving anddistributing information, application of new technical andtechnological solutions (CPS, RDS, TMC), development andimprovement of the information and communication infrastructure,data exchange network, introduction of navigationsystems, etc.